The Tourism Industry Before and After the Pandemic Covid-19 - Nur Wardina Mardhiyyah binti Mat Arof; Nur Athirah Atikah binti Khairul Jazli; Wan Aisya Syafiqah binti Abdul Rahman; Nurul Nasrin Fatin binti Mohd Hisham; Nurshafikah Zulaikha binti Abdul Razak (Jurnal Pariwisata Nusantara (JUWITA), 2022)
Purpose: The purpose of this study is to investigate the Covid-19 pandemic's impact on different sectors, which in this case is the tourism industry Method: This study collects data from previous research from 2020 – 2022 and the recent statistical data gathered from the authorities' website sources to evaluate recent research on the impact of the Covid-19 pandemic on tourism sectors. Result: The global economic effects have forced significant adjustments in how firms may respond to and adapt to consumers' changing purchasing behaviors. That defines the tourism sector's decrease in the whole pandemic era before and after the COVID-19 pandemic. Contribution: With this research, we hope it can help the community understand this matter better and that people will also know about this matter and how to overcome it.